Edukasi Literasi Keuangan dan Penguatan Kemampuan Numerasi melalui Program Menabung Kreatif dan Matematika Dasar di SDN Locare 1 Bondowoso - Rassya Muhammad Yusuf; Hafsa Aulia Az-Zahra; Annida Nur Noviyanti; Andini Salsabila Firdausa; Ifatul Rojannah; Fardha Maria Dwi Zakiya Rahma; Agung Nugroho Puspito (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Financial literacy and character education are essential competencies that should be introduced to children from an early age. This community service activity aims to enhance fourth- and fifth-grade students’ understanding of basic financial management and to instill character values through the Smart Piggy Bank Pancasila program at SDN Locare 1 Bondowoso. Using a Participatory Action Research (PAR) approach with a learning-by-doing method, the program includes financial literacy education, numeracy skills, simple cash recording, creating piggy banks from recycled materials, and community activities. Evaluation results show an increase in students’ average scores from 4 to 21 in financial literacy, from 27 to 33 in numeracy, and from 71 to 72 in cash recording. The program effectively promotes financial knowledge, character development, and responsible habits among elementary students.